Electrostatic spinning nanofiber porous membrane for protective clothing

By using electrospinning technology to prepare composite porous membranes in protective clothing, the problem of insufficient breathability and comfort of protective clothing is solved, and the effect of high breathability, moisture permeability and good mechanical properties is achieved. It is suitable for medical and protective clothing.

CN119800606AActive Publication Date: 2025-04-11ZHANGJIAGANG HONGYU ARTIFICIAL LEATHER

Patent Information

Application Number
CN202510283940.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-11
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

The existing protective clothing has poor breathability and comfort, which leads to discomfort for staff when wearing it for a long time. The electrospinned nanofiber porous membrane has poor stability and insufficient puncture resistance, which limits its application in protective clothing.

Method used

Polyvinylidene fluoride, titanium dioxide, graphene oxide aerogel, collagen and carbon nanotubes are used to prepare porous membranes through coaxial electrospinning technology to form a composite structure of the shell and core layer to improve the stability and performance of the porous membrane.

Benefits of technology

It realizes the high breathability, moisture permeability and good mechanical properties of protective clothing, improves wear comfort and puncture resistance, and is suitable for medical clothing and protective clothing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800606A_ABST
    Figure CN119800606A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nanofiber porous membranes, in particular to an electrostatic spinning nanofiber porous membrane for protective clothing. The electrostatic spinning nanofiber porous membrane for the protective clothing is prepared from the following raw materials in parts by mass: 5 to 15 parts of polyvinylidene fluoride, 1 to 2 parts of zirconium chloride, 5 to 15 parts of titanium dioxide aerogel, 0.5 to 1.5 parts of 2-aminoterephthalic acid, 1 to 3 parts of glacial acetic acid, 1 to 5 parts of collagen and 1 to 2 parts of carbon nanotubes. The titanium dioxide aerogel is prepared by the following steps: adding butyl titanate and graphene oxide into ethanol, uniformly stirring, adjusting the pH value of the system to 3-4, stirring for 10-20 minutes, standing for 1-2 hours at 60-70 DEG C, filtering, washing, drying, crushing, mixing with carboxyl-terminated polyamidoamine, adding into water, carrying out ultrasonic treatment, freezing, carrying out vacuum drying, and crushing. The composite film is excellent in structural stability, good in barrier property, high in puncture-resistant strength and excellent in moisture penetrability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanofiber porous membranes, and in particular to an electrostatically spun nanofiber porous membrane for protective clothing. Background Art

[0002] The existing protective clothing has poor air permeability, and workers who wear medical protective clothing for a long time will feel uncomfortable. This discomfort is closely related to the air permeability, moisture permeability, thermal and moisture resistance, etc. of the materials used in the protective clothing. However, comfort is usually opposite to protective performance. Therefore, it is necessary to improve the comfort of protective clothing fabrics as much as possible while meeting the protective performance of protective clothing.

[0003] The porous structure of the fiber can also improve the water absorption and air permeability of textiles to a great extent. Therefore, constructing fibers with a porous structure can be an effective means. Due to its own properties, polyvinylidene fluoride (PVDF) has good chemical stability, acid and alkali resistance, oxidation resistance, and aging resistance. Electrospinning has good air permeability due to its unique three-dimensional stacking structure, which can be used to improve the wearing comfort of protective clothing. The use of electrospinning to prepare PVDF nanofiber porous membranes for use in protective clothing has excellent research prospects.

[0004] CN 103263856 A discloses a method for preparing an electrostatically spun hydrophobic nanofiber porous membrane for membrane distillation, comprising: dissolving a hydrophobic functional polymer material in a solvent to obtain a 1-35wt% polymer spinning solution, performing electrostatic spinning to obtain a hydrophobic nanofiber porous membrane, and then performing heat treatment to obtain an electrostatically spun hydrophobic nanofiber porous membrane for membrane distillation. The method can improve the defects of low water flux and easy wetting of membrane pores of a conventional membrane distillation membrane, but has poor stability.

[0005] Electrospinning can produce nano or submicron fibers. The pore size of the resulting nanofiber porous membrane is between tens of nanometers and tens of microns, and the pores have good connectivity. However, the porous membrane has poor structural stability and is prone to rupture when used in protective clothing due to its puncture resistance, which greatly limits its development and application and needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an electrostatically spun nanofiber porous membrane for protective clothing.

[0007] The invention discloses an electrostatically spun nanofiber porous membrane for protective clothing. The raw materials thereof include, by weight, 5-15 parts of polyvinylidene fluoride, 1-2 parts of zirconium chloride, 5-15 parts of titanium dioxide aerogel, 0.5-1.5 parts of 2-aminoterephthalic acid, 1-3 parts of glacial acetic acid, 1-5 parts of collagen and 1-2 parts of carbon nanotubes.

[0008] Preferably, the electrospun nanofiber porous membrane of the protective clothing has a porosity of 75-82.4% and a thickness of 150-210 μm.

[0009] Preferably, titanium dioxide aerogel is prepared by the following steps: adding butyl titanate and graphene oxide to ethanol and stirring evenly, adjusting the pH value of the system to 3-4, stirring for 10-20 minutes, standing at 60-70°C for 1-2 hours, filtering, washing, drying, crushing, mixing with terminal carboxyl polyamide amine, adding to water for ultrasonic treatment for 1-2 hours, freezing at -60 to -40°C for 1-3 hours, vacuum drying, and crushing.

[0010] Preferably, the mass ratio of butyl titanate, graphene oxide and carboxyl-terminated polyamidoamine is 5-15:1-2:1-3; and the generation number of the carboxyl-terminated polyamidoamine is 2.0-4.0.

[0011] Preferably, the ultrasound frequency is 10-15 kHz.

[0012] The method for preparing the electrospun nanofiber porous membrane for protective clothing comprises the following steps: S1, adding zirconium chloride to N,N-dimethylformamide and stirring evenly, adding titanium dioxide aerogel thereto and ultrasonically treating for 2-4 hours, adding 2-aminoterephthalic acid and glacial acetic acid thereto, solvent thermally reacting at 90-100°C for 5-15 hours, cooling to room temperature, washing, and vacuum drying to obtain loaded titanium dioxide; S2, adding polyvinylidene fluoride and loaded titanium dioxide into hexafluoroisopropanol and stirring evenly to obtain a prefabricated shell mixture; S3, adding collagen and carbon nanotubes into hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Coaxially electrospin the prefabricated shell layer mixture and the prefabricated core layer mixture onto the surface of a metal drum, the electrospinning voltage is 18-20 kV, and the distance between the spinning nozzle and the metal drum is 10-12 cm; heat treatment at 70-80° C. for 10-15 h.

[0013] Preferably, in S1, the ultrasonic frequency is 10-15 kHz.

[0014] Preferably, in S4, during the coaxial electrospinning process, the prefabricated shell layer mixture is injected into the outer needle of the coaxial electrospinning needle, and the prefabricated core layer mixture is injected into the inner needle of the coaxial electrospinning needle. The inner diameter of the outer needle is 1-1.2 mm, and the inner diameter of the inner needle is 0.6-0.8 mm. The inner layer liquid inlet speed is controlled to be 0.1-0.4 mL / min, and the outer layer liquid inlet speed is 1-1.5 mL / min.

[0015] A protective suit comprises, from inside to outside, polyester fabric, the above-mentioned protective suit electrostatically spun nanofiber porous membrane, non-woven fabric, the above-mentioned protective suit electrostatically spun nanofiber porous membrane, and polyester / polypropylene fabric.

[0016] Preferably, the mass ratio of polyester to polypropylene in the polyester / polypropylene fabric is 50:50, and the surface density of the polyester / polypropylene fabric is 120-140g / m 2 .

[0017] Preferably, the surface density of the polyester fabric is 90-110 g / m 2 .

[0018] Preferably, the surface density of the nonwoven fabric is 50-70 g / m 2 .

[0019] Beneficial effects:

[0020] The present invention dopes graphene oxide into titanium dioxide, and then combines it with terminal carboxyl polyamide amine to form aerogel. The graphene oxide presents a hydrophilic sheet structure and cooperates with the dendritic macromolecular polyamide amine. The obtained aerogel structure not only has good air permeability, but also has excellent thermal and moisture conductivity. At the same time, MOFs are in situ grown on the aerogel through solvent thermal reaction, and the growth of MOFs is effectively inhibited by the structure of the titanium dioxide aerogel, so that the loaded titanium dioxide has good stability, a large specific surface area and a high porosity. The fabric formed by compounding with polyvinylidene fluoride has good softness and can ensure that it has excellent mechanical strength and high tear resistance.

[0021] The present invention compounds polyvinylidene fluoride and loaded titanium dioxide as the shell layer, and compounds collagen and carbon nanotubes as the core layer. Through coaxial electrospinning, a porous network structure is formed to ensure that the porous membrane has good uniformity, high porosity and good air permeability, so that air and moisture can be effectively diffused from the skin into the environment, and the moisture permeability is excellent; at the same time, it has low thermal resistance, can effectively transfer the heat generated by the human body to the environment through the fabric, and has good wearing comfort.

[0022] The porous membrane obtained by the present invention has excellent structural stability, good barrier properties, high puncture resistance, and excellent moisture permeability, can effectively reduce the feeling of stuffiness when worn, and has excellent wearing comfort, and is particularly suitable for medical clothing and protective clothing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a comparison chart of the rigidity of the electrospun nanofiber porous membranes in protective clothing obtained in Example 5 and Comparative Examples 1-3.

[0024] Figure 2 This is a comparison chart of the air permeability and moisture permeability of the electrospun nanofiber porous membrane in the protective clothing obtained in Example 5 and Comparative Examples 1-3.

[0025] Figure 3 This is a comparison chart of the tear strength and breaking strength of protective clothing prepared by using the electrospun nanofiber porous membrane obtained in Example 5 and Comparative Examples 1-3.

[0026] Figure 4 This is a comparison chart of the puncture resistance and thermal resistance of protective clothing prepared by using the electrospun nanofiber porous membrane obtained in Example 5 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0027] The present invention will be further explained below in conjunction with specific embodiments.

[0028] Example 1

[0029] The invention discloses an electrostatically spun nanofiber porous membrane for protective clothing, wherein the raw materials thereof include: 50 g of polyvinylidene fluoride, 10 g of zirconium chloride, 50 g of titanium dioxide aerogel, 5 g of 2-aminoterephthalic acid, 10 g of glacial acetic acid, 10 g of collagen, and 10 g of carbon nanotubes.

[0030] Titanium dioxide aerogel is prepared by the following steps: 50g of butyl titanate and 10g of graphene oxide are added to 300g of ethanol and stirred evenly, the pH value of the system is adjusted to 3-4 with nitric acid solution, stirred at a speed of 1000r / min for 10min, allowed to stand at a temperature of 60°C for 1h, filtered, washed, dried at a temperature of 100°C, crushed, mixed with 10g of 2.0-generation terminal carboxyl polyamide amine, added to 400g of water, ultrasonically treated for 1h, the ultrasonic frequency was 10kHz, frozen at a temperature of -60°C for 1h, vacuum dried, and crushed.

[0031] The method for preparing the electrospun nanofiber porous membrane for protective clothing comprises the following steps: S1, adding zirconium chloride to 500g N,N-dimethylformamide and stirring evenly, adding titanium dioxide aerogel thereto and ultrasonically treating for 2h, the ultrasonic frequency is 10kHz, adding 2-aminoterephthalic acid and glacial acetic acid thereto, solvent thermally reacting at a temperature of 90°C for 5h, cooling to room temperature, washing once with ethanol, and vacuum drying to obtain loaded titanium dioxide; S2, adding polyvinylidene fluoride and supported titanium dioxide into 200 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated shell layer mixture; S3, adding collagen and carbon nanotubes to 50 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Inject the prefabricated shell layer mixture into the outer needle of the coaxial electrospinning needle, and inject the prefabricated core layer mixture into the inner needle of the coaxial electrospinning needle, wherein the inner diameter of the outer needle is 1mm, and the inner diameter of the inner needle is 0.6mm, and the inner layer liquid inlet speed is controlled to be 0.1mL / min, and the outer layer liquid inlet speed is 1mL / min; electrospinning treatment, the electrospinning voltage is 18kV, the distance between the spinning nozzle and the metal drum is 10cm, and the speed of the metal drum is 200r / min; remove the film from the surface of the metal drum and heat treat it at 70℃ for 10h.

[0032] Example 2

[0033] The invention discloses an electrostatically spun nanofiber porous membrane for protective clothing, wherein the raw materials thereof include: 150 g of polyvinylidene fluoride, 20 g of zirconium chloride, 150 g of titanium dioxide aerogel, 15 g of 2-aminoterephthalic acid, 30 g of glacial acetic acid, 50 g of collagen, and 20 g of carbon nanotubes.

[0034] Titanium dioxide aerogel is prepared by the following steps: 150g of butyl titanate and 20g of graphene oxide are added to 600g of ethanol and stirred evenly, the pH value of the system is adjusted to 3-4 with nitric acid solution, stirred at a speed of 2000r / min for 20min, allowed to stand at a temperature of 70°C for 2h, filtered, washed, dried at a temperature of 110°C, crushed, mixed with 30g of 4.0-generation terminal carboxyl polyamide amine, added to 1000g of water, ultrasonically treated for 2h, the ultrasonic frequency was 15kHz, frozen at a temperature of -40°C for 3h, vacuum dried, and crushed.

[0035] The method for preparing the electrospun nanofiber porous membrane for protective clothing comprises the following steps: S1, adding zirconium chloride to 1000g N,N-dimethylformamide and stirring evenly, adding titanium dioxide aerogel thereto and ultrasonically treating for 4h, the ultrasonic frequency is 15kHz, adding 2-aminoterephthalic acid and glacial acetic acid thereto, solvent thermally reacting at a temperature of 100°C for 15h, cooling to room temperature, washing with ethanol for 3 times, and vacuum drying to obtain loaded titanium dioxide; S2, adding polyvinylidene fluoride and supported titanium dioxide into 300 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated shell mixture; S3, adding collagen and carbon nanotubes to 150 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Inject the prefabricated shell layer mixture into the outer needle of the coaxial electrospinning needle, and inject the prefabricated core layer mixture into the inner needle of the coaxial electrospinning needle, wherein the inner diameter of the outer needle is 1.2mm, and the inner diameter of the inner needle is 0.8mm. Control the inner layer liquid inlet speed to be 0.4mL / min, and the outer layer liquid inlet speed to be 1.5mL / min; electrospinning treatment, the electrospinning voltage is 20kV, the distance between the spinning nozzle and the metal drum is 12cm, and the metal drum speed is 450r / min; remove the film from the surface of the metal drum and heat treat it at 80℃ for 15h.

[0036] Example 3

[0037] The invention discloses an electrostatically spun nanofiber porous membrane for protective clothing, wherein the raw materials thereof include: 80 g of polyvinylidene fluoride, 18 g of zirconium chloride, 80 g of titanium dioxide aerogel, 12 g of 2-aminoterephthalic acid, 15 g of glacial acetic acid, 40 g of collagen, and 13 g of carbon nanotubes.

[0038] Titanium dioxide aerogel is prepared by the following steps: 120g of butyl titanate and 13g of graphene oxide are added to 500g of ethanol and stirred evenly, the pH value of the system is adjusted to 3-4 with nitric acid solution, stirred at a speed of 1200r / min for 18min, allowed to stand at a temperature of 64°C for 100min, filtered, washed, dried at a temperature of 102°C, crushed, mixed with 25g of 3.0-generation terminal carboxyl polyamide amine, added to 600g of water, ultrasonically treated for 100min, the ultrasonic frequency was 11kHz, frozen at a temperature of -45°C for 1.5h, vacuum dried, and crushed.

[0039] The method for preparing the electrospun nanofiber porous membrane for protective clothing comprises the following steps: S1. Add zirconium chloride to 900 g of N,N-dimethylformamide and stir evenly, add titanium dioxide aerogel thereto and ultrasonically treat for 2.5 h at an ultrasonic frequency of 13 kHz, add 2-aminoterephthalic acid and glacial acetic acid thereto, and perform solvent thermal reaction at a temperature of 92 ° C for 12 h, cool to room temperature, wash twice with ethanol, and vacuum dry to obtain loaded titanium dioxide; S2, adding polyvinylidene fluoride and supported titanium dioxide into 220 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated shell mixture; S3, adding collagen and carbon nanotubes to 120 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Inject the prefabricated shell layer mixture into the outer needle of the coaxial electrospinning needle, and inject the prefabricated core layer mixture into the inner needle of the coaxial electrospinning needle, wherein the inner diameter of the outer needle is 1.1 mm, and the inner diameter of the inner needle is 0.7 mm. Control the inner layer liquid inlet speed to be 0.2 mL / min, and the outer layer liquid inlet speed to be 1.4 mL / min; perform electrospinning treatment, the electrospinning voltage is 18.5 kV, the distance between the spinning nozzle and the metal drum is 11.5 cm, and the rotation speed of the metal drum is 300 r / min; remove the film from the surface of the metal drum, and heat treat it at 77°C for 11 hours.

[0040] Example 4

[0041] The invention discloses an electrostatically spun nanofiber porous membrane for protective clothing, wherein the raw materials thereof include: 120g of polyvinylidene fluoride, 12g of zirconium chloride, 120g of titanium dioxide aerogel, 8g of 2-aminoterephthalic acid, 25g of glacial acetic acid, 20g of collagen, and 17g of carbon nanotubes.

[0042] Titanium dioxide aerogel is prepared by the following steps: 80g of butyl titanate and 17g of graphene oxide are added to 400g of ethanol and stirred evenly, the pH value of the system is adjusted to 3-4 with nitric acid solution, stirred at a speed of 1800r / min for 12min, allowed to stand at a temperature of 66°C for 80min, filtered, washed, dried at a temperature of 108°C, crushed, mixed with 15g of 3.0-generation terminal carboxyl polyamide amine, added to 800g of water, ultrasonically treated for 80min, the ultrasonic frequency was 13kHz, frozen at a temperature of -55°C for 2.5h, vacuum dried, and crushed.

[0043] The method for preparing the electrospun nanofiber porous membrane for protective clothing comprises the following steps: S1, adding zirconium chloride to 700g N,N-dimethylformamide and stirring evenly, adding titanium dioxide aerogel thereto and ultrasonically treating for 3.5h, the ultrasonic frequency is 11kHz, adding 2-aminoterephthalic acid and glacial acetic acid thereto, solvent thermally reacting at a temperature of 98°C for 8h, cooling to room temperature, washing with ethanol twice, and vacuum drying to obtain loaded titanium dioxide; S2, adding polyvinylidene fluoride and supported titanium dioxide into 280 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated shell layer mixture; S3, adding collagen and carbon nanotubes to 80 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Inject the prefabricated shell layer mixture into the outer needle of the coaxial electrospinning needle, and inject the prefabricated core layer mixture into the inner needle of the coaxial electrospinning needle, wherein the inner diameter of the outer needle is 1.1 mm, and the inner diameter of the inner needle is 0.7 mm. Control the inner layer liquid inlet speed to be 0.3 mL / min, and the outer layer liquid inlet speed to be 1.2 mL / min; perform electrospinning treatment, the electrospinning voltage is 19.5 kV, the distance between the spinning nozzle and the metal drum is 10.5 cm, and the speed of the metal drum is 400 r / min; remove the film from the surface of the metal drum, and heat treat it at 73°C for 13 hours.

[0044] Example 5

[0045] The invention discloses an electrostatically spun nanofiber porous membrane for protective clothing, wherein the raw materials thereof include: 100 g of polyvinylidene fluoride, 15 g of zirconium chloride, 100 g of titanium dioxide aerogel, 10 g of 2-aminoterephthalic acid, 20 g of glacial acetic acid, 30 g of collagen, and 15 g of carbon nanotubes.

[0046] Titanium dioxide aerogel is prepared by the following steps: 100g of butyl titanate and 15g of graphene oxide are added to 450g of ethanol and stirred evenly, the pH value of the system is adjusted to 3-4 with nitric acid solution, stirred at a speed of 1500r / min for 15min, allowed to stand at a temperature of 65°C for 90min, filtered, washed, dried at a temperature of 105°C, crushed, mixed with 20g of 3.0-generation terminal carboxyl polyamide amine, added to 700g of water, ultrasonically treated for 90min, the ultrasonic frequency was 12kHz, frozen at a temperature of -40°C for 2h, vacuum dried, and crushed.

[0047] The method for preparing the electrospun nanofiber porous membrane for protective clothing comprises the following steps: S1, adding zirconium chloride to 800g N,N-dimethylformamide and stirring evenly, adding titanium dioxide aerogel thereto and ultrasonically treating for 3h, the ultrasonic frequency is 12kHz, adding 2-aminoterephthalic acid and glacial acetic acid thereto, solvent thermally reacting at a temperature of 95°C for 10h, cooling to room temperature, washing with ethanol twice, and vacuum drying to obtain loaded titanium dioxide; S2, adding polyvinylidene fluoride and supported titanium dioxide into 250 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated shell layer mixture; S3, adding collagen and carbon nanotubes to 100 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Inject the prefabricated shell layer mixture into the outer needle of the coaxial electrospinning needle, and inject the prefabricated core layer mixture into the inner needle of the coaxial electrospinning needle, wherein the inner diameter of the outer needle is 1.1mm, and the inner diameter of the inner needle is 0.7mm. Control the inner layer liquid inlet speed to be 0.25mL / min, and the outer layer liquid inlet speed to be 1.3mL / min; perform electrospinning treatment, the electrospinning voltage is 19kV, the distance between the spinning nozzle and the metal drum is 11cm, and the speed of the metal drum is 350r / min; remove the film from the surface of the metal drum, and heat treat it at 75℃ for 12h.

[0048] Comparative Example 1 Disclosed is an electrostatically spun nanofiber porous membrane for protective clothing, the raw materials of which include: 100g of polyvinylidene fluoride, 145g of titanium dioxide aerogel, 30g of collagen, and 15g of carbon nanotubes.

[0049] Titanium dioxide aerogel is prepared by the following steps: 100g of butyl titanate and 15g of graphene oxide are added to 450g of ethanol and stirred evenly, the pH value of the system is adjusted to 3-4 with nitric acid solution, stirred at a speed of 1500r / min for 15min, allowed to stand at a temperature of 65°C for 90min, filtered, washed, dried at a temperature of 105°C, crushed, mixed with 20g of 3.0-generation terminal carboxyl polyamide amine, added to 700g of water, ultrasonically treated for 90min, the ultrasonic frequency was 12kHz, frozen at a temperature of -40°C for 2h, vacuum dried, and crushed.

[0050] The method for preparing the electrospun nanofiber porous membrane for protective clothing comprises the following steps: S1. Add polyvinylidene fluoride and titanium dioxide aerogel into 250 g of hexafluoroisopropanol and stir evenly to obtain a prefabricated shell mixture; S3, adding collagen and carbon nanotubes to 100 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Inject the prefabricated shell layer mixture into the outer needle of the coaxial electrospinning needle, and inject the prefabricated core layer mixture into the inner needle of the coaxial electrospinning needle, wherein the inner diameter of the outer needle is 1.1mm, and the inner diameter of the inner needle is 0.7mm. Control the inner layer liquid inlet speed to be 0.25mL / min, and the outer layer liquid inlet speed to be 1.3mL / min; perform electrospinning treatment, the electrospinning voltage is 19kV, the distance between the spinning nozzle and the metal drum is 11cm, and the speed of the metal drum is 350r / min; remove the film from the surface of the metal drum, and heat treat it at 75℃ for 12h.

[0051] Comparative Example 2 The invention discloses an electrostatically spun nanofiber porous membrane for protective clothing, wherein the raw materials thereof include: 100 g of polyvinylidene fluoride, 15 g of zirconium chloride, 100 g of titanium dioxide aerogel, 10 g of 2-aminoterephthalic acid, 20 g of glacial acetic acid, 30 g of collagen, and 15 g of carbon nanotubes.

[0052] Titanium dioxide aerogel is prepared by the following steps: 100g of butyl titanate is added to 450g of ethanol and stirred evenly, a nitric acid solution is used to adjust the pH value of the system to 3-4, stirring at a speed of 1500r / min for 15min, standing at a temperature of 65°C for 90min, filtering, washing, drying at a temperature of 105°C, crushing, mixing with 20g of 3.0-generation terminal carboxyl polyamide amine, adding to 700g of water and ultrasonically treating for 90min, the ultrasonic frequency is 12kHz, freezing at a temperature of -40°C for 2h, vacuum drying, crushing, adding 15g of graphene oxide and mixing evenly.

[0053] The method for preparing the electrospun nanofiber porous membrane for protective clothing comprises the following steps: S1, adding zirconium chloride to 800g N,N-dimethylformamide and stirring evenly, adding titanium dioxide aerogel thereto and ultrasonically treating for 3h, the ultrasonic frequency is 12kHz, adding 2-aminoterephthalic acid and glacial acetic acid thereto, solvent thermally reacting at a temperature of 95°C for 10h, cooling to room temperature, washing with ethanol twice, and vacuum drying to obtain loaded titanium dioxide; S2, adding polyvinylidene fluoride and supported titanium dioxide into 250 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated shell layer mixture; S3, adding collagen and carbon nanotubes to 100 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Inject the prefabricated shell layer mixture into the outer needle of the coaxial electrospinning needle, and inject the prefabricated core layer mixture into the inner needle of the coaxial electrospinning needle, wherein the inner diameter of the outer needle is 1.1mm, and the inner diameter of the inner needle is 0.7mm. Control the inner layer liquid inlet speed to be 0.25mL / min, and the outer layer liquid inlet speed to be 1.3mL / min; perform electrospinning treatment, the electrospinning voltage is 19kV, the distance between the spinning nozzle and the metal drum is 11cm, and the speed of the metal drum is 350r / min; remove the film from the surface of the metal drum, and heat treat it at 75℃ for 12h.

[0054] Comparative Example 3 The invention discloses an electrostatically spun nanofiber porous membrane for protective clothing, wherein the raw materials thereof include: 100 g of polyvinylidene fluoride, 15 g of zirconium chloride, 100 g of titanium dioxide aerogel, 10 g of 2-aminoterephthalic acid, 20 g of glacial acetic acid, 30 g of collagen, and 15 g of carbon nanotubes.

[0055] Titanium dioxide aerogel is prepared by the following steps: 100g of butyl titanate and 15g of graphene oxide are added to 450g of ethanol and stirred evenly, the pH value of the system is adjusted to 3-4 with a nitric acid solution, stirred at a speed of 1500r / min for 15min, allowed to stand at a temperature of 65°C for 90min, filtered, washed, dried at a temperature of 105°C, crushed, added to 700g of water and ultrasonically treated for 90min, the ultrasonic frequency was 12kHz, frozen at a temperature of -40°C for 2h, vacuum dried, crushed, and mixed evenly with 20g of 3.0-generation terminal carboxyl polyamide amine.

[0056] The method for preparing the electrospun nanofiber porous membrane for protective clothing comprises the following steps: S1, adding zirconium chloride to 800g N,N-dimethylformamide and stirring evenly, adding titanium dioxide aerogel thereto and ultrasonically treating for 3h, the ultrasonic frequency is 12kHz, adding 2-aminoterephthalic acid and glacial acetic acid thereto, solvent thermally reacting at a temperature of 95°C for 10h, cooling to room temperature, washing with ethanol twice, and vacuum drying to obtain loaded titanium dioxide; S2, adding polyvinylidene fluoride and supported titanium dioxide into 250 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated shell layer mixture; S3, adding collagen and carbon nanotubes to 100 g of hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Inject the prefabricated shell layer mixture into the outer needle of the coaxial electrospinning needle, and inject the prefabricated core layer mixture into the inner needle of the coaxial electrospinning needle, wherein the inner diameter of the outer needle is 1.1mm, and the inner diameter of the inner needle is 0.7mm. Control the inner layer liquid inlet speed to be 0.25mL / min, and the outer layer liquid inlet speed to be 1.3mL / min; perform electrospinning treatment, the electrospinning voltage is 19kV, the distance between the spinning nozzle and the metal drum is 11cm, and the speed of the metal drum is 350r / min; remove the film from the surface of the metal drum, and heat treat it at 75℃ for 12h.

[0057] The softness of the electrospun nanofiber porous membranes in the protective clothing obtained in Example 5 and Comparative Examples 1-3 was tested using the Kawabata evaluation system (KES-FB).

[0058] like Figure 1 As shown in the figure, the rigidity of the electrospun nanofiber porous membrane of the protective clothing obtained in Example 5 is the lowest, which is only 0.2267 gf.cm 2 / cm, that is, the softness is the highest, which is better than that of comparative examples 1-3 (P < 0.05).

[0059] With reference to GB / T 24218.15-2018 “Test methods for nonwoven fabrics for textiles Part 15: Determination of air permeability”, the air permeability of the electrospun nanofiber porous membranes in the protective clothing obtained in Example 5 and Comparative Examples 1-3 was measured by the pressure difference method (100 Pa).

[0060] With reference to GB / T 12704.1-2009 “Test method for water vapor permeability of textile fabrics Part 1: Moisture absorption method”, the water vapor permeability of the electrospun nanofiber porous membranes in the protective clothing obtained in Example 5 and Comparative Examples 1-3 was measured.

[0061] like Figure 2 As shown, the air permeability and moisture permeability of the electrospun nanofiber porous membrane in the protective clothing obtained in Example 5 are the highest, which are better than those in Comparative Examples 1-3 (P < 0.05).

[0062] Protective clothing is prepared by using the electrospun nanofiber porous membrane obtained in Example 5 and Comparative Examples 1-3. Each group of protective clothing includes, from the inside to the outside: a surface density of 100 g / m 2 The polyester fabrics, the electrospun nanofiber porous membranes of each group of protective clothing, and the surface density of 60g / m 2 Non-woven fabrics, each group of protective clothing is electrospun nanofiber porous membrane, with a surface density of 130g / m 2 Polyester / polypropylene (mass ratio 50 / 50) fabric.

[0063] The tear strength, breaking strength and puncture resistance of the above-mentioned protective clothing were measured with reference to GB 19082-2023 "Disposable Protective Clothing for Medical Use". The thermal resistance of the above-mentioned protective clothing was measured with reference to GB / T 11048-2018 "Determination of thermal and moisture resistance of textiles under steady-state conditions for physiological comfort (evaporative hot plate method)".

[0064] like Figure 3 and Figure 4 As shown, the protective clothing prepared by the electrospun nanofiber porous membrane using the protective clothing obtained in Example 5 has the highest tear strength, breaking strength and puncture resistance, and small thermal resistance, indicating that the protective clothing prepared by the electrospun nanofiber porous membrane using the protective clothing obtained in Example 5 has excellent mechanical properties and can effectively transfer the heat generated by the human body to the environment through the fabric.

[0065] This is because the present invention dopes graphene oxide into titanium dioxide and then combines it with terminal carboxyl polyamide amine to form aerogel. The graphene oxide presents a hydrophilic sheet structure and cooperates with the dendritic macromolecular polyamide amine. The obtained aerogel structure not only has good air permeability, but also has excellent thermal and moisture conductivity. At the same time, MOFs are in situ grown on the aerogel through solvent thermal reaction, and the growth of MOFs is effectively inhibited by the structure of titanium dioxide aerogel, so that the loaded titanium dioxide has good stability, large specific surface area and high porosity. The fabric formed by compounding with polyvinylidene fluoride has good softness and can ensure that it has excellent mechanical strength and high tear resistance. The present invention further compounds polyvinylidene fluoride and loaded titanium dioxide as a shell layer, and compounds collagen and carbon nanotubes as a core layer, and through coaxial electrospinning, a porous network structure is formed to ensure that the porous membrane has good uniformity, high porosity and good air permeability, so that air and moisture can be effectively diffused from the skin into the environment, and the moisture permeability is excellent; at the same time, it has low thermal resistance, can effectively transfer the heat generated by the human body to the environment through the fabric, and has good wearing comfort.

[0066] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An electrospun nanofiber porous membrane for protective clothing, characterized in that: The raw materials include, by weight: 5-15 parts of polyvinylidene fluoride, 1-2 parts of zirconium chloride, 5-15 parts of titanium dioxide aerogel, 0.5-1.5 parts of 2-aminoterephthalic acid, 1-3 parts of glacial acetic acid, 1-5 parts of collagen and 1-2 parts of carbon nanotubes.

2. The electrospun nanofiber porous membrane for protective clothing according to claim 1, characterized in that: Its porosity is 75-82.4% and its thickness is 150-210μm.

3. The electrospun nanofiber porous membrane for protective clothing according to claim 1, characterized in that: Titanium dioxide aerogel is prepared by the following steps: adding butyl titanate and graphene oxide to ethanol and stirring evenly, adjusting the pH value of the system to 3-4, stirring for 10-20 minutes, standing at 60-70°C for 1-2 hours, filtering, washing, drying, crushing, mixing with terminal carboxyl polyamide amine, adding to water for ultrasonic treatment for 1-2 hours, freezing at -60 to -40°C for 1-3 hours, vacuum drying, and crushing.

4. The electrospun nanofiber porous membrane for protective clothing according to claim 3, characterized in that: The mass ratio of butyl titanate, graphene oxide and carboxyl-terminated polyamidoamine is 5-15:1-2:1-3; the generation number of carboxyl-terminated polyamidoamine is 2.0-4.

0.

5. The electrospun nanofiber porous membrane for protective clothing according to claim 3, characterized in that: Ultrasonic frequency 10-15kHz.

6. A method for preparing an electrospun nanofiber porous membrane for protective clothing as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1, adding zirconium chloride to N,N-dimethylformamide and stirring evenly, adding titanium dioxide aerogel thereto and ultrasonically treating for 2-4 hours, adding 2-aminoterephthalic acid and glacial acetic acid thereto, solvent thermally reacting at 90-100°C for 5-15 hours, cooling to room temperature, washing, and vacuum drying to obtain loaded titanium dioxide; S2, adding polyvinylidene fluoride and loaded titanium dioxide into hexafluoroisopropanol and stirring evenly to obtain a prefabricated shell mixture; S3, adding collagen and carbon nanotubes into hexafluoroisopropanol and stirring evenly to obtain a prefabricated core layer mixture; S4. Coaxially electrospin the prefabricated shell layer mixture and the prefabricated core layer mixture onto the surface of a metal drum, the electrospinning voltage is 18-20 kV, and the distance between the spinning nozzle and the metal drum is 10-12 cm; heat treatment at 70-80° C. for 10-15 h.

7. The method for preparing the electrospun nanofiber porous membrane for protective clothing according to claim 6, characterized in that: In S1, the ultrasound frequency is 10-15kHz.

8. The method for preparing the electrospun nanofiber porous membrane for protective clothing according to claim 6, characterized in that: In S4, during the coaxial electrospinning process, the prefabricated shell layer mixture is injected into the outer needle of the coaxial electrospinning needle, and the prefabricated core layer mixture is injected into the inner needle of the coaxial electrospinning needle. The inner diameter of the outer needle is 1-1.2 mm, and the inner diameter of the inner needle is 0.6-0.8 mm. The inner layer liquid inlet speed is controlled to be 0.1-0.4 mL / min, and the outer layer liquid inlet speed is 1-1.5 mL / min.

9. A protective clothing, characterized in that: From the inside out, they include: polyester fabric, the electrospun nanofiber porous membrane for protective clothing as described in any one of claims 1 to 5, non-woven fabric, the electrospun nanofiber porous membrane for protective clothing as described in any one of claims 1 to 5, and polyester / polypropylene fabric.

10. The protective clothing according to claim 9, characterized in that: The mass ratio of polyester to polypropylene in polyester / polypropylene fabric is 50:50; the surface density of polyester fabric is 90-110g / m 2 The surface density of non-woven fabric is 50-70g / m 2 , the surface density of polyester / polypropylene fabric is 120-140g / m 2。

Citation Information

Patent Citations

  • Preparation method of electrostatic spinning hydrophobic nanofiber porous membrane for membrane distillation

    CN103263856A

  • Polymer-ceramic compound nanometer fibrous membrane as well as preparation method and application thereof

    CN102242464A

  • Inorganic / organic composite polyimide-based nanofiber membranes, their preparation methods and applications

    CN102277648A

  • Electrostatic spinning nanofiber membrane as well as preparation method thereof

    CN103437071A

  • Nanofiber composite air filter paper and production method thereof

    CN106012652A

Cited By

  • Micro-hook stab-resistant inner core with cross-layer gallium-based alloy synergistic heat conduction and preparation method and application of micro-hook stab-resistant inner core

    CN122008655A